The Hydroida of the Pacific Coast of North America - Torrey H.B. (University of California Publications Zoology, 1902)
Descriptors: Campalecium medusiferum, Corymorpha palma, Hydractinia milleri, Aglaophenia inconspicua, Diplocheilus allmani, Halecium annulatum, Halecium kofoidi, Antennella avalonia, Pycnotheca allmani, Plumularia alicia, Abietinaria traski, Sertularia traski, Salacia desmoides, Sertularia desmoides, Symplectoscyphus dentiferus, Sertularella dentifera, Bimeria robusta, Garveia franciscana, Bimeria franciscana, Garveia robusta, Eudendrium californicum